Pengaruh Variasi Konsentrasi NaOH Terhadap Xerogel dari Kulit Durian (Durio zibethinus Murr.) - Anjelia, Mariza; Nasra, Edi; Kurniawati, Desy; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
The objective of this study was to synthesize xerogel from durian peel waste by determining the optimal NaOH concentration for the synthesis process. The sol-gel method was employed, utilizing SiO2 as the main component and Na2SiO3 as the precursor. The sodium silicate precursor was obtained by reacting SiO2 derived from durian shell ash with NaOH solutions of various concentrations: 2 M, 5 M, 8 M, 11 M, and 14 M. The surface area of the resulting xerogel was tested, and the optimal NaOH concentration was found to be 8 M, yielding a surface area of 6637.8 m2/g. The synthesized xerogel was further characterized using FTIR analysis within the wave number range of 4000-600 cm-1. The FTIR data revealed the presence of silanol at a wave number of 3253.30 cm-1 and siloxane at a wave number of 1060.18 cm-1, confirming the successful synthesis of the xerogel.